2022
DOI: 10.3390/nu14193889
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Nicotinamide Riboside in Health and Diseases

Abstract: Among all the NAD+ precursors, nicotinamide riboside (NR) has gained the most attention as a potent NAD+-enhancement agent. This recently discovered vitamin, B3, has demonstrated excellent safety and efficacy profiles and is orally bioavailable in humans. Boosting intracellular NAD+ concentrations using NR has been shown to provide protective effects against a broad spectrum of pathological conditions, such as neurodegenerative diseases, diabetes, and hearing loss. In this review, an integrated overview of NR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…NR has the potential to improve both congenital and acquired heart failure 42 . Furthermore, NR may also have systemic effects, particularly in liver metabolism, insulin antagonism, and skeletal muscle function, which can be altered in conjunction with heart defects 43 . When NR treatment is performed, the induction level of Myh7 in SRFHKO mice is limited, and Myh7 induction is a signal of heart stress and metabolic remodeling in heart failure 44 .…”
Section: The Relationship Between Nad + and Heart ...mentioning
confidence: 99%
“…NR has the potential to improve both congenital and acquired heart failure 42 . Furthermore, NR may also have systemic effects, particularly in liver metabolism, insulin antagonism, and skeletal muscle function, which can be altered in conjunction with heart defects 43 . When NR treatment is performed, the induction level of Myh7 in SRFHKO mice is limited, and Myh7 induction is a signal of heart stress and metabolic remodeling in heart failure 44 .…”
Section: The Relationship Between Nad + and Heart ...mentioning
confidence: 99%
“…NR has been found to ameliorate tissue nicotinamide adenine dinucleotide (NAD + ) depletion induced by acute kidney injury via increases in autophagy and SIRT1. The induction of NAD + has protective effects against numerous conditions, including diabetes, obesity [19], neurodegenerative diseases, and noise-induced hearing loss [20][21][22]. Lapato et al reported that NR supplementation enhances muscle mitochondrial biogenesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous beneficial effects of NR have been reported in neurological disorders. For instance, NR has been shown to increase NAD + , reduce DNA damage, ameliorate neuroinflammation, attenuate cellular apoptosis, and improve hippocampal synaptic plasticity in diabetic mice and mouse models of Alzheimer's disease [21,22]. The administration of NR increased NAD + levels and significantly suppressed inflammation in the brain [23,24].…”
Section: Introductionmentioning
confidence: 99%